Solid-Phase Synthesis of ɤ-Lactone and 1,2-Oxazine Derivatives and Their Efficient Chiral Analysis - Krupkova, Sona; Aguete, Gonzalo Pazos; Kocmanova, Leona; Volna, Tereza; Grepl, Martin; Novakova, Lucie; Miller, Marvin John; Hlavac, Jan (PloS one, 2016)
Derivatives of 3-methyl-3,6-dihydro-2H-1,2-oxazine-6-carboxylic acid prepared by regioselective hetero Diels-Alder reaction of arylnitroso compounds with sorbic acid were used for solid-phase synthesis of a library of derivatives that included modification of carboxylic group, dihydroxylation of double bond and cleavage of N-O bond. Derivatives of 2,3,4-trihydroxyhexanoic acid obtained from 3,6-dihydro-2H-1,2-oxazines after double bond dihydroxylation and N-O cleavage were used for simple and stereoselective formation of chiral lactones derived from 3,4-dihydroxydihydrofuran-2(3H)-one. The final compounds obtained as a mixture of stereoisomers were analyzed with use of chiral HPLC and SFC. HPLC analyses were not successful for all derivatives or required lengthy chromatography. On the other hand SFC afforded much shorter analyses and was effective for all studied derivatives. The method of synthesis and analysis is thus suitable for future study of stereoselective synthesis of lactones and other derivatives from single oxazine derivatives and application of high-throughput synthesis on solid-support and combinatorial chemistry.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; Cycloaddition Reaction; Oxazines; laktony; vysokoúčinná kapalinová chromatografie; Solid-Phase Synthesis Techniques; magnetická rezonanční spektroskopie; Chromatography, High Pressure Liquid; cykloadiční reakce; Magnetic Resonance Spectroscopy; Lactones; Stereoisomerism; stereoizomerie; techniky syntézy na pevné fázi; oxaziny